Understanding the Values of Truth, Goodness, Morals, and Character in the Educational Process - Meikajandi, Zamzam; Naffakhatusofwa, Nela; Udin, Tamsik (Penerbit Hellow Pustaka, 2026)
The increasing signs of moral degradation among students indicate that the educational process has not yet fully succeeded in shaping character as a real behavioral orientation. Character education should not be understood merely as the transmission of normative values, but must be positioned as a continuous process of internalizing the values of truth and goodness. This study aims to analyze the role of the values of truth and goodness in shaping students’ morals and character through the educational process. The research employs a qualitative approach using a literature review method of national and international scholarly publications, books, and relevant policy documents published within the last ten years. The findings show that the effectiveness of character education is largely determined by the integration of moral knowledge, moral sensitivity, and moral action. The values of truth and goodness function as ethical foundations that guide character formation; however, their implementation remains constrained by cognitively oriented learning practices and the challenges of digital culture. This study emphasizes the importance of a holistic approach to character education through role modeling, habituation, and collaboration among schools, families, and communities.